Intercultural communication competence: A case study of international students' intercultural intelligence in Malaysia - Mardhiyyah - Mardhiyyah; Mohd. Amirul Hafidz Ahmat; Berliani Ardha; Al-Mansor Bin Abu Said (Bricolage : Jurnal Magister Ilmu Komunikasi, 2022)
The experience of everyday intercultural communication events and encounters will always shape one's intercultural communication perspective. This perspective is also fully interwoven in our deeply held beliefs and values, which guide our thoughts and actions both within and across cultural boundaries, as well as our understandings of the other cultures we encounter. Therefore, it is a must to have intercultural communication competence in crossing these cultural differences. This study aims to develop Intercultural Communication Competence: a Case Study on Intercultural Intelligence of International students in Melaka, Malaysia. Using the concept of Intercultural Communication Competence, this study investigates studies related to the intercultural communication competence of international students in Melaka, Malaysia. The paradigm used in this study is constructivism. This study uses a qualitative method with a single case study design and data collection techniques with interviews and documentation studies. The subjects of this research are international students studying in Malaysia. Miles and Huberman’s data analysis technique was used in this study, which includes three activities, namely data reduction, data presentation, and conclusion drawing (verification). The findings of this study provide a description of international students' intercultural communication competence as evidenced by their attitudes, skills, knowledge, and behavior in accepting a culture other than their own. They have a strong desire to be able to adapt to a new culture, even though they are frequently hampered by language differences and stereotypes during the adaptation process.Keywords:  Intercultural, communication, competence, foreign  student